Is post orthognathic maxillary sinusitis related to sino-nasal anatomical alterations?. Issue 6 (June 2019) - Procacci, Pasquale; Lanaro, Luca; Trevisiol, Lorenzo; Bertossi, Dario; Zotti, Francesca; Fabio, Lonardi; D'Agostino, Antonio
Abstract: Le Fort I osteotomies have been used for more than five decades, but their impact on nasal and paranasal cavities physiology, has not been studied deeply. In this paper we want to analyse the possible correlation between post-orthognathic findings and prevalence of sinusitis which require surgical treatment. A retrospective cohort study was designed in 2017; the study was designed and carried out in the Verona University maxillo-facial department, a referral centre for orthognathic surgery. The study population is made of 64 patients that underwent orthognathic surgery (To treat class II or III malocclusion) between 2010 and 2015. Inclusion criteria were the availability of a Cone Beam Computed Tomography (CBCT) before surgery and one between 12 and 24 months after orthognathic surgery. Exclusion criteria were smoking habit and previous orthognathic procedures. During follow-up time prevalence of sinusitis was 18.5% and some patients required a secondary surgery to treat sinusitis. Surgery induced anatomic alterations were frequent in patients with sinusitis, sings and symptoms of sinusitis show positive correlation with anatomic alterations.